The Images of Expanding the Constitutional Judge's Supervisory Function in Algeria - Raddaoui, Mourad (Journal of Legal Studies and Researches, 2023)
This article deals with the scope of expanding the constitutional judge's monitoring function in Algeria. The study concludes that the expansion of the constitutional judge's oversight function is reflected in two forms: the expansion of the constitutional bloc and the adoption of the interpretative reservations technique.